Halal certification in slaugtering industry: issues, problems and actions (persijilan halal dalam industri sembelihan: isu, masalah dan tindakan) - Ghazali, Mohd Al'Ikhsan; Awang, Md Daud; Md Sawari, Siti Salwa; Yunos, Nasruddin; Saroji, Azis Jakfar (Laboratory of Halal Policy and Management, Halal Products Research Institute, Universiti Putra Malaysia, 2018)
Halal certification in Malaysia has been growing rapidly to several industries including the slaughtering industry. A continuous halal control needs to be properly executed to ensure that the process meets the halalan toyyiba. The industry of poultry processing has now become a globally-cultivated field. The application of the latest technology is inevitable but must be comply with the Shariah rules and regulations that have been outlined by the authorities. The principle of fixed and flexible (thabat dan murunah) in Islam has never contradict with the development of science and technology. The halal processing chain, especially at slaughtering premises, is very vulnerable to inaccuracy. The failure of the industry to meet the halalan toyyiba aspects can adversely affect the quality of the slaughtered products and even more serious, a non-halal slaughter. Ulama and Islamic Scholar are always willing to deal with severe parties to discussing regarding to the latest technology as not contradict with the Shari'a. Hence, The Islamic Religious Department throughout Malaysia government has implemented a Halal Critical Control Point which is a risky part for the incidence of inefficiency contamination in the slaughter process. Although, the tight monitoring has been instigated to ensure the halal quality but non-compliance issues are still addressed. JAKIM has itemized categories of offenses and actions to any party who do not comply the rules through the issue of incompatibility in slaughtering industry. The higher authorities need to monitor continuously and immediate action should be taken for improving the quality of halal regulation management internally and also assisting in the enhancement of halal management.